2018
DOI: 10.2739/kurumemedj.ms652008
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat/High-Sucrose Diet Induces WNT4 Expression in Mouse Pancreatic β-cells

Abstract: Surplus intake of dietary fat and sugar is closely related to the pathogenesis of type 2 diabetes. Mice fed a high-fat/high-sucrose (HF/HS) diet develop insulin resistance and hyperinsulinemia, and exhibit hyperplasia of pancreatic β-cells [1]. Susceptibility and phenotype vary depending on the genetic background,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…Previous studies showed that insulin secretion of β -cell line MIN6 increased significantly at high glucose concentration, and its insulin secretion and S-type response curve were similar to those of normal islet cells. Further studies on insulin secretion, glucose transport, glycooxidative phosphorylation, and glucose utilization of insulin β -cell line MIN6 showed that the cell components in MIN6 cells that regulate glucose concentration-dependent insulin secretion are similar to normal islets in quality and quantity [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that insulin secretion of β -cell line MIN6 increased significantly at high glucose concentration, and its insulin secretion and S-type response curve were similar to those of normal islet cells. Further studies on insulin secretion, glucose transport, glycooxidative phosphorylation, and glucose utilization of insulin β -cell line MIN6 showed that the cell components in MIN6 cells that regulate glucose concentration-dependent insulin secretion are similar to normal islets in quality and quantity [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, FZD3 was proved to be required for the development of embryonic pancreas in mice [40]. FZD4 may be involved in the regulation of β-cell functions in mouse [41]. More gene and clinical evidence are needed to explore their potential values.…”
Section: Discussionmentioning
confidence: 99%
“…57 Similarly, cellular proliferation and GSIS of β-cell line MIN6 are not affected when exposed to Wnt4 protein, but suppressed significantly when knockdown of Wnt4. 58 therefore, restoring Wnt4 or Wnt5a significantly alleviates TGF-β1mediated fibrosis in diabetic kidneys. 62 Similarly, melatonin, simvastatin, Salvia miltiorrhiza extracts and liraglutide treatment block the apoptosis of mesangial cells and improve the renal injury of diabetic rat by restoring the canonical Wnt signalling mediated by Wnt4 and Wnt5a.…”
Section: Wnt4mentioning
confidence: 91%
“…Wnt5b expression is up-regulated in islets of mice fed with high-fat diet (HFD), and UK Caucasian individuals carrying IVS3C>G variant (rs2270031) in the Wnt5b gene are predispose to T2DM. 58,98 Although the exact role of Wnt5b in the regulation of β-cell proliferation and functions has not been elucidated, silencing the noncanonical Wnt pathways induced by Wnt4/Wnt5a/Wnt5b and canonical Wnt3a/β-catenin signalling together could drive the immature hiPSC-derived S7 cells towards a mature phenotype, indicating the potential inhibitory effect of Wnt5b on the maturation of β-cells. 48 Subsequent in vitro experiments showed that compared with the inhibitory effect on adipogenesis via activation of canonical Wnt signalling mediated by Wnt1 and Wnt10b, Wnt5b…”
Section: Wnt5a and Wnt5bmentioning
confidence: 99%